Indian monsoon variability during the past ∼8.5 cal kyr as recorded in the sediments of the northeastern Arabian Sea. (30th December 2022) - Ravichandran, M.; Gupta, Anil K.; Mohan, K.; Tiwari, Sameer K.; Lakshumanan, C.; Panigrahi, M.K.
Abstract: We analyzed benthic and planktic foraminifera, total organic carbon and stable isotopes ratios of carbon and oxygen from 100 samples of marine sediment Core ABP, 25/03, off Gujarat in the northeastern Arabian Sea. Factor and cluster analyses of thirty highest-ranked benthic foraminifer species enabled to identify seven biofacies in the study sequence characterizing major changes in deep-sea environments during the past ∼8.5 cal kyr. The benthic foraminiferal data has been combined with population abundances of upwelling indicator planktic foraminifer Globigerina bulloides and mixed layer species from Core ABP, 25/03 and compared with that from ODP Hole 723A and Core ABP, 25/02, western and eastern Arabian Sea, respectively. A major change in benthic foraminifera occurs during ∼8.5 to 6 cal kyr BP, when the summer monsoon was stronger whereas during 6 to 2 cal kyr BP, the data suggest a weak summer monsoon. Planktic foraminifer Globigerina bulloides does not show any significant trend in the study core, but deep thermocline species Neogloboquadrina dutertrei and mixed layer species show significant trend with an inverse correlation with the TOC. This core records high TOC from ∼6.5 to 4 cal kyr BP and during the last 2 cal kyr and low TOC during ∼8.5 to 6.5 cal kyr BP and 4 to 2 cal kyr BP. It is interesting to note intervals of high mixed layer species coincide with high Neogloboquadrina dutertrei percentages and low TOC values at Core ABP, 25/03 during 8.5 to 6.5 cal kyr BP .The faunal data is supported by carbon and oxygen isotope ratios (δ 13 C and δ 18 O) of shells of benthic foraminifer Cibicides spp. to strengthen our understanding of changes in the eastern Arabian Sea since ∼8.5 cal kyr BP .